Methamphetamine signals transcription of IL1β and TNFα in a reactive oxygen species-dependent manner and interacts with HIV-1 Tat to decrease antioxidant defense mechanisms - Basova, Liana V.; Vien, Whitney; Bortell, Nikki; Najera, Julia A.; Marcondes, Maria Cecilia Garibaldi (Frontiers in Cellular Neuroscience, 2022)
Methamphetamine (Meth) abuse is a common HIV co-morbidity that is linked to aggravated Central Nervous System (CNS) inflammation, which accentuates HIV- associated neurological dis-orders, triggered both directly or indirectly by the drug. We used the well-established human innate immune macrophage cell line system (THP1) to demonstrate that Reactive Oxygen Species (ROS) immediately induced by Meth play a role in the increased transcription of inflammatory genes, in in-teraction with HIV-1 Tat peptide. Meth and Tat, alone and together, affect early events of transcrip-tional activity, as indicated by changes in RNA polymerase (RNAPol) recruitment patterns through-out the genome, via ROS-dependent and -independent mechanisms. IL1eta (IL1) and TNF alpha (TNF), two genes with defining roles in the inflammatory response, were both activated in a ROS-dependent manner. We found that this effect occurred via the activation of the activator protein 1 (AP-1) comprising cFOS and cJUN transcription factors and regulated by the SRC kinase. HIV-1 Tat, which was also able to induce the production of ROS, did not further impact the effects of ROS in the context of Meth, but promoted gene activity independently from ROS, via additional transcription fac-tors. For instance, HIV-1 Tat increased NFkB activation and activated gene clusters regulated by Tata box binding peptide, ING4 and IRF2. Importantly, HIV-1 Tat decreased the expression of anti-oxidant genes, where its suppression of the detoxifying machinery may contribute to the aggrava-tion of oxidative stress induced by ROS in the context of Meth. Our results provide evidence of ef-fects of Meth via ROS and interactions with HIV Tat that promote the transcription of inflammatory genes such as IL1and TNF.